2018
DOI: 10.1021/acs.jmedchem.7b01647
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 7-Oxo-2,4,5,7-tetrahydro-6H-pyrazolo[3,4-c]pyridine Derivatives as Potent, Orally Available, and Brain-Penetrating Receptor Interacting Protein 1 (RIP1) Kinase Inhibitors: Analysis of Structure–Kinetic Relationships

Abstract: We report the discovery of 7-oxo-2,4,5,7-tetrahydro-6 H-pyrazolo[3,4- c]pyridine derivatives as a novel class of receptor interacting protein 1 (RIP1) kinase inhibitors. On the basis of the overlay study between HTS hit 10 and GSK2982772 (6) in RIP1 kinase, we designed and synthesized a novel class of RIP1 kinase inhibitor 11 possessing moderate RIP1 kinase inhibitory activity and P-gp mediated efflux. The optimization of the core structure and the exploration of appropriate substituents utilizing SBDD approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 41 publications
3
80
0
Order By: Relevance
“…Further molecular dynamic simulation study revealed that NTB451 indeed interacted with K45 of RIPK1, which mediates kinase activity. NTB451 has a structural similarity at their benzyl-triazol moiety with some known RIPK1 inhibitors, Nec-1, GSK 2982772 [ 23 , 36 ]. However, the functional relationship of such moiety needs to be elaborately studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further molecular dynamic simulation study revealed that NTB451 indeed interacted with K45 of RIPK1, which mediates kinase activity. NTB451 has a structural similarity at their benzyl-triazol moiety with some known RIPK1 inhibitors, Nec-1, GSK 2982772 [ 23 , 36 ]. However, the functional relationship of such moiety needs to be elaborately studied.…”
Section: Discussionmentioning
confidence: 99%
“…We used this program to generate the initial docking poses of NTB451 and U0126, which were needed for the following molecular dynamics (MD) simulation study. The crystal structure of RIP1 kinase, bound to inhibitor (PDB ID: 6C3E) [ 36 ] with a resolution of 2.6 Å, was used for the validation of the docking simulation. The active site of RIPK1 was defined from the bound inhibitor, 2-benzyl-5-nitro-1H-benzimidazole, within a radius of 10 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased cFLIP and reduced levels of activated Casp8 in patients with MS, and thus decreased Casp8 inactivating cleavage of RIPK1, likely explain the increased RIPK1 kinase activity and necroptosis seen in MS. Genetic ( Ripk1 D138N/D138N ) and pharmacological (Nec-1s) inhibition of RIPK1 kinase ameliorated disease pathology, improved animal behaviour, attenuated the production of pro-inflammatory cytokines and decreased recruitment of immune cells in two animal models of MS 3 . Another inhibitor of RIPK1 kinase developed by Takeda also showed efficacy in an animal model of MS 98 .…”
Section: Ripk1 In Immune and Autoinflammatory Diseasesmentioning
confidence: 99%
“…A subsequent family of benzoxazepinone RIPK1 inhibitors was published by GlaxoSmithKline (GSK), which included GSK′481 and the clinical candidate GSK′772 (refs 173 , 174 ), which was followed by the identification of a dihydropyrazole chemotype of RIPK1 inhibitors including GSK′963 and GSK′547 (refs 175 , 176 ). Published and patented compounds generated by Takeda, Genentech and Rigel are all from the same benzoxazepinone family as the GSK′481 series 177 – 179 .
Fig.
…”
Section: Clinical Development Of Ripk1 Inhibitorsmentioning
confidence: 99%
“…The 7‐ and 8‐positions on the benzoxazepinone core of receptor interacting protein 1 (RIP1) kinase inhibitor 94 are exposed to the solvent‐accessible region. Consequently, optimization of the center platform and careful modification of neighboring substituents by utilizing structure‐based design resulted in the identification of the cyanosubstituted derivative 95 as a highly active and brain‐penetrating RIP1 kinase inhibitor with favorable oral bioavailability and excellent ADMET properties ( t 1/2 = 210 minutes, in human and mouse liver microsomes; high plasma exposure (AUC = 658 ng/h/mL) and a moderate plasma duration (mean residence time, MRT = 3.1 hour in mice) (Figure E) …”
Section: Exploitation Of Solvent‐exposed Regions For Structure‐based mentioning
confidence: 99%